Assessing the Impact of Drought on Agricultural Production and Proposing the Conversion of Suitable Cropping Systems in Thach Ha District, Ha Tinh Province - Quoc Viet, Nguyen; Anh Hung, Pham; Thi Hong, Tran; Thi Kim Dung, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 4DO - 10.25073/2588-1094/vnuees.4410, 2019)
Drought has occurred in most communes in Thach Ha district with a mild level. The drought is milder in the Eastern coastal communes of the district while the Western and Southwestern communes of the district are more severely affected by drought. Drought has a significant impact on agricultural production, drought makes 56.3% of households surveyed lose completely (losing completely or having to replant), 29.8% of households lost most seasons and more than 10% of households lose their crops in half. In order to overcome the ongoing drought situation and to effectively use the agricultural land resources of Thach Ha district, this study uses a method of Land suitability classifications considering the impact of drought and Thach's development orientation is the basis for the proposed the conversion of suitable cropping systems. The results of the proposed land use of Thach Ha district are as follows: The paddy rice land area (2-3 paddy rice crops per year) is 8,674.93 ha, accounting for 24.52% of the natural land area; Paddy rice and annual crops (1 paddy rice crop and 1-2 annual crops) covers an area of ​​1,691.41 ha, accounting for 4.78% of natural land area; Annual crops and short-term industrial plants with an area of ​​2,911.32 ha, accounting for 8.23% of natural land area; agro-forestry land with an area of ​​1,695.29 hectares, accounting for 4.79% of natural land area; aquaculture land has an area of ​​1,803.87 ha, accounting for 5.1% of the natural land area; forest land (production forest and coastal protection forest) covers an area of ​​8,643.71 ha, accounting for 24.42% of natural land area.